A Future for Simulation in Acute Neurology - Wijdicks, Eelco F. M.; Hocker, Sara E. (Seminars in Neurology, 2018)
Acute neurologic (and potentially disability prone) conditions are rarely taught and, if so, at the bedside and usually after the fact. Simulation training offers a realistic environment to teach rapid-fire decision making, how to take charge, and how best to approach a deteriorating, acutely ill neurologic patient.Simulating acute neurology is a newly emerging educational program. Proven principles of simulation, which may include teaching technical skills, can be applied to acute neurology (and neurointensive care). Communication skills pertaining to catastrophic neurologic injury with all its ethical ramifications can be taught and practiced. There is a growing need for well-designed, tested teaching scenarios and a need to validate this approach. This review provides an overview of the potential opportunities available in medical institutions with a simulation center.
Keywords: simulation; skills; procedures; education; acute brain injury